2016
DOI: 10.1016/j.jvs.2016.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mesenteric ischemia outcome analysis and predictors of endovascular failure

Abstract: Objective: Outcomes of open revascularization (OR) and endovascular revascularization (ER) for chronic mesenteric ischemia (CMI) were analyzed to identify predictors of endovascular failure. Methods: A retrospective study was performed of all consecutive patients with CMI (161 patients, 215 vessels) treated from 2008 to 2012. Demographics, comorbidities, clinical presentation, etiology, and treatment modalities were compared. Outcomes included technical success, restenosis requiring reintervention, complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
11
2
2
Order By: Relevance
“…13 Recent studies have demonstrated that patients after ET who presented with clinical recurrence or required reintervention appeared to have longer lesions (!2 cm), nominal stent diameter 5 mm, residual stenosis !40%, and higher rates of aortic occlusive disease. 14,15 Oderich et al 16 reported a nonrandomized comparison of covered versus bare metal stents in 225 patients treated for CMI. In their study, covered stents outperformed bare metal stents, with lower rates of restenosis, symptom recurrence, and reintervention and improved patency rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Recent studies have demonstrated that patients after ET who presented with clinical recurrence or required reintervention appeared to have longer lesions (!2 cm), nominal stent diameter 5 mm, residual stenosis !40%, and higher rates of aortic occlusive disease. 14,15 Oderich et al 16 reported a nonrandomized comparison of covered versus bare metal stents in 225 patients treated for CMI. In their study, covered stents outperformed bare metal stents, with lower rates of restenosis, symptom recurrence, and reintervention and improved patency rates.…”
Section: Discussionmentioning
confidence: 99%
“…22 Because of differences in the comorbidities and the difficulty in comparing the outcomes in patients treated with OSR versus ET, the establishment of treatment guidelines is particularly difficult. 14 Lejay et al reported that the complete OSR of visceral arteries for CMI provided lasting results, despite high morbidity. The 30-day mortality and morbidity rates were 3.5% and 13.9%, respectively, with a median follow-up of 6.9 years, while the primary patency rate was not statistically different between the complete revascularization group (84%) and the incomplete revascularization group (87%) at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…La cirugía ofrece mayor probabilidad de permeabilidad vascular a cinco años [20][21][22][23] . Con el tratamiento endovascular, se reducen las complicaciones posquirúrgicas, la estancia hospitalaria, el costo, la invasión para el paciente y las complicaciones anestésicas 24,25 .…”
Section: Discussionunclassified
“…En comparación con la cirugía, se encontró que, en los casos de tratamiento endovascular los pacientes eran más ancianos (73 Vs. 66 años; p=0,014) y había mayor tasa de lesiones cortas (≤2 cm) en el angiograma (23 Vs. 47 %; p=0,004), menor tasa de permeabilidad vascular a los tres años (91 Vs. 74 %; p=0,018), mayor supervivencia (95 Vs. 78 %; p=0,003), y estancia más corta en la unidad de cuidados intensivos (p<0,001); no hubo diferencia en la mortalidad entre ambos grupos (5,2 Vs. 11 %; p=0,165). Al analizar los casos de fracaso terapéutico, se encontró que, con el tratamiento endovascular, había mayor tasa de enfermedad aórtica oclusiva (86 Vs. 49 %, p=0,005), lesiones más largas (57 Vs. 12 %; p<0,001) y mayor mortalidad perioperatoria (15 Vs. 2 %; p=0,009) 24 .…”
Section: Discussionunclassified
“…Chronic mesenteric ischemia (CMI) is a severe disease characterized by postprandial pain and weight loss and occurs when visceral vessels develop high-grade stenosis or occlusion [ 1 , 2 ]. Early therapy for the symptomatic disease is important to prevent cachexia and end-organ ischemia, associated with high mortality of 50–69% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%